PRIORITIES OF RISK-MANAGEMENT ORGANIZATION IN KAZAKHSTAN COMMERCIAL BANKS (Journal of Economic Research & Business Administration, 2015)
"The organization of the risk management in commercial banks under the market economy is especially relevant. The credit portfolio is the set of requirements on bank credits, which is classified on criteria related to the various forms of credit risk analysis."
Keywords: RISK-MANAGEMENT ORGANIZATION